DEVELOPING ENVIRONMENT BASED PICTURIAL STORYBOOK MEDIA FOR GRADE IV STUDENTS OF SDN 013 KARIMUN - Muhiri; Tisrin Maulina Dewi; Raja Mitha Karina (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to see the feasibility of the product developed in the form of an environmental-based picture storybook for grade four students. The subjects in this study were ten students at grade V. The type of research was research and development which was modified into seven steps, namely: (1) Data collection/planning (2) Product design (3) Product design validation (4) Product revision (5) Teacher response (6 ) Field trial (7) Data analysis. The instruments in this study were interviews with teachers and questionnaires given to design experts, material experts, homeroom teachers for grade IV and ten grade four students. The results of this study consisted of (1) Validation by design experts obtained a score of 4.22 in the "Very feasible" category (2) Validation by material experts obtained a score of 4.50 in the "Very feasible" category (3) Validation by homeroom teachers for grade four obtained a score of 4.94 categories “Very decent” (4) Validation by Grade V elementary school students scored 4.33 in the “Very decent” category. From the data obtained, this study concluded that the environmental-based picture storybook media product for grade four students at SDN 013 Karimun with an average score of 4.50 in the "Very feasible" category could be an alternative teaching material at schools.